2006
DOI: 10.1007/s10140-006-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant endogenous Klebsiella pneumoniae endophthalmitis: imaging findings

Abstract: Endogenous endophthalmitis is a rare but serious complication of Klebsiella pneumoniae infection that has been predominantly reported to occur in diabetic patients of East Asian origin with K. pneumoniae liver abscesses. The clinical symptoms and signs of endogenous endophthalmitis are nonspecific and may mimic other causes of an acute non-traumatic eye. Permanent visual loss and blindness are common sequelae because of delayed diagnosis and treatment. Computed tomography and magnetic resonance imaging can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The most common ophthalmic complication of K. pneumoniae infection is endophthalmitis (1)(2)(3)(4). Our patient did not have any apparent ophthalmic complications except unilateral optic neuritis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The most common ophthalmic complication of K. pneumoniae infection is endophthalmitis (1)(2)(3)(4). Our patient did not have any apparent ophthalmic complications except unilateral optic neuritis.…”
Section: Discussionmentioning
confidence: 62%
“…K lebsiella pneumonitis can lead to endophthalmitis, especially in patients who also have pyogenic liver abscess or diabetes (1)(2)(3)(4). We report a patient who developed optic neuritis without evidence of endophthalmitis in the setting of Klebsiella pneumonitis, liver abscess, and cerebral microabscesses, a clinical circumstance not described previously.…”
mentioning
confidence: 69%
“…The MRI fi ndings of endogenous endophthalmitis include increased T1-weighted signal intensity of the vitreous and a thickened irregular uveoscleral coat with intense gadolinium-enhancement. Seale et al [ 19 ] demonstrated superiority of fl uid-attenuated inversion recovery and diffusion-weighted imaging in demonstrating intraocular abscesses. However, because these are case and small series reports, an impact on prognosis was not shown.…”
Section: Diagnosis Of Ekementioning
confidence: 98%
“…Because of globe hyperintensity on DWI and corresponding hypointensity on ADC mapping are suggesting intra-ocular or subretinal abscess formation (4), they are useful factors for the diagnosis of endogenous endophthalmitis, and hyperintensity on FLAIR imaging also suggests endogenous endophthalmitis. Although the best imaging tool for diagnosis of brain abscess (5), gadolinium-enhanced T1-weighted imaging is useless in the diagnosis of endophthalmitis because of the vitreous humor is avascular and an intravitreous abscess may not produce an enhancing wall before the occurrence of inflammatory neovascularization (4,6). In the current case, as mentioned above, DWI, ADC and FLAIR sequences were useful for diagnosing endophthalmitis, and DWI and ADC were also valuable to reach the diagnosis of brain abscess.…”
Section: Index Words : Endophthalmitis•brain Abscess•magnetic Resonanmentioning
confidence: 99%